2019
DOI: 10.1111/srt.12785
|View full text |Cite
|
Sign up to set email alerts
|

Application of parelectric spectroscopy to detect skin cancer—A pilot study

Abstract: Background The early detection of skin cancer is still challenging and calls for objective, fast diagnostic, and ideally non‐invasive methods in order to leave the potentially malignant tumor cells unaltered. In this paper, the parelectric spectroscopy was applied to evaluate the potential of a non‐invasive detection of basal cell carcinoma (BCC) and malignant melanoma. Materials and Methods A prototype of parelectric spectroscopy was used to investigate non‐invasively dipole density and mobility of suspicious… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…A study (65) detailing the performance of a multitiered system of decision support system reported that the inclusion of the EIS score in clinical decision making led to a reduction in the number of unneeded biopsies and that the amount of the reduction depends on a clinician's experience, i.e., 14.8% for resident, 16.8% for midlevel, and 16% for practicing dermatologist. More recently, a paraelectric spectroscopy technology has been used for skin cancer application in a correlational study (64).…”
Section: Skin Electrical Measurementsmentioning
confidence: 99%
“…A study (65) detailing the performance of a multitiered system of decision support system reported that the inclusion of the EIS score in clinical decision making led to a reduction in the number of unneeded biopsies and that the amount of the reduction depends on a clinician's experience, i.e., 14.8% for resident, 16.8% for midlevel, and 16% for practicing dermatologist. More recently, a paraelectric spectroscopy technology has been used for skin cancer application in a correlational study (64).…”
Section: Skin Electrical Measurementsmentioning
confidence: 99%
“…However, clinical examination depends on experience, even when it is enhanced by dermoscopy [2]. Some new optical methods have been tested and introduced in clinical practice in order to facilitate a more accurate diagnosis, Raman spectroscopy and optical coherence tomography being the most used [3], while many others like hyperspectral imaging (HSI) [4] or parelectric spectroscopy [5] are still in the experimental stage. These methods need trained personnel in order to add more accuracy to clinical examination.…”
Section: Introductionmentioning
confidence: 99%